English Language Learning in Higher Classes at an Elementary School Using the RADEC Learning Model with 6Cs Orientation - Wulandari, Bunga Ayu; Destrinelli, Destrinelli; Ridha, Ahmad; Sopandi, Wahyu (Universitas Pendidikan Ganesha, 2025)
English language learning in higher elementary school grades still faces challenges in effectively integrating 21st-century skills, thus requiring an instructional model that can simultaneously foster character, citizenship, critical thinking, creativity, collaboration, and communication, such as the RADEC model with a 6Cs orientation. This study examines the influence of the RADEC (Read-Answer-Discuss-Explain-Create) learning model on enhancing 21st-century skills—Character, Citizenship, Critical Thinking, Creativity, Collaboration, and Communication (6Cs)—among sixth-grade elementary students in English language learning. Utilising a one-group pretest-posttest design, the research involved 20 students aged around 12 years over eight meetings. Data were gathered using instruments constructed to evaluate cognitive and behavioural competencies aligned with the 6Cs framework. The results, analyzed using the Wilcoxon Signed-Rank Test, indicated statistically significant improvements across all six skills (p < 0.05), with large effect sizes (r > 0.8), highlighting the substantial influence of the RADEC learning model. These findings suggest that the RADEC learning model encourages active participation, independent learning, and collaboration, making it a promising instructional model for cultivating essential 21st-century competencies in primary education. Further research is recommended to explore its application across diverse student populations and educational contexts.